2008
DOI: 10.1074/jbc.m803634200
|View full text |Cite
|
Sign up to set email alerts
|

Galectin-3 Regulates Integrin α2β1-mediated Adhesion to Collagen-I and -IV

Abstract: Galectins are a taxonomically widespread family of galactose-binding proteins of which galectin-3 is known to modulate cell adhesion. Using single cell force spectroscopy, the contribution of galectin-3 to the adhesion of Madin-Darby canine kidney (MDCK) cells to different extracellular matrix proteins was investigated. When adhering to collagen-I or -IV, some cells rapidly entered an enhanced adhesion state, marked by a significant increase in the force required for cell detachment. Galectin-3-depleted cells … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
60
0
1

Year Published

2010
2010
2014
2014

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 87 publications
(62 citation statements)
references
References 47 publications
1
60
0
1
Order By: Relevance
“…Gal3 has been reported to regulate cell-cell adhesion and other key homeostatic properties such as cell-matrix adhesion, proliferation, and differentiation by associating with N-cadherin, ␤1 integrin, epithelial growth factor receptor, and transforming growth factor ␤ receptor (32)(33)(34)(35)(36)(37)(38)(39). We observed that Gal3 association with Dsg2 is mediated by N-linked glycans on Dsg2 and that this lactose-sensitive interaction promotes Dsg2 stability at the cell surface and epithelial intercellular adhesion.…”
mentioning
confidence: 65%
“…Gal3 has been reported to regulate cell-cell adhesion and other key homeostatic properties such as cell-matrix adhesion, proliferation, and differentiation by associating with N-cadherin, ␤1 integrin, epithelial growth factor receptor, and transforming growth factor ␤ receptor (32)(33)(34)(35)(36)(37)(38)(39). We observed that Gal3 association with Dsg2 is mediated by N-linked glycans on Dsg2 and that this lactose-sensitive interaction promotes Dsg2 stability at the cell surface and epithelial intercellular adhesion.…”
mentioning
confidence: 65%
“…Our liver-aggressive cells also showed an enhanced ability to interact with type IV collagen. The a 2 b 1 -integrin, which can interact with type IV collagen (Magro et al, 1997;Friedrichs et al, 2008), has been associated with gastric cancer carcinoma lymph node and liver metastasis (Ura et al, 1998). The use of an antagonist of a 2 b 1 has been reported to decrease the extravasation into the liver and micrometastasis associated with colorectal and hepatocellular carcinoma cell lines (Rosenow et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…Thus Gal-3 does not seem to affect multiple types of cell proliferation in the adult SVZ. Apart from its proliferative role, Gal-3 is also known to act as an adhesion and de-adhesion molecule (Friedrichs et al, 2008) and its pattern of expression in the SVZ led us to study neuroblast migration. Furthermore, Gal-3 binds -galactoside residues on EGFR, laminin, 1 integrin, NCAM and tenascin, all of which influence SVZ neuroblast migration (Aguirre et al, 2005;Cremer et al, 1994;Emsley and Hagg, 2003;Ghashghaei et al, 2007;Kim et al, 2009).…”
Section: Gal-3 Maintains Normal Svz Neuroblast Migrationmentioning
confidence: 99%